Performance of MIMO CDMA in Impulsive Channels - Hilal, Hasan Saed Abu (Eastern Mediterranean University (EMU), 2012)
ABSTRACT: In this thesis, multiple-input and multiple-output (MIMO) communication systems, in code division multiple access (CDMA) settings, and vertical-bell layered space time (VBLAST) algorithms are investigated. The performance of linear CDMA detectors, operating in an environment with interference due to non-Gaussian noise and time mismatch is considered. The robust successive interference cancellation (RSIC) and robust space time decorrelating detectors (RSTDD) are employed to detect the signals received by multi receiving antennas having time mismatches. The performance of the detectors in practical situations such as incomplete channel state information, corre- lated antennas, and impulsive noise is investigated. The results show that RSIC and RDD have a good performance in adverse conditions. The performance of the DD in MIMO CDMA system under two different impulsive noise models is examined. A robust detection technique is proposed to overcome the impulsive effect on the system. Maximal ratio combining (MRC) and post detection combining (PDC) are used to achieve diversity reception. We show that the proposed RDD outperforms the linear decorrelating detector (DD) consistently for the ideal and power imbalanced cases. Furthermore, we analyzed and derived the probability of bit error (Pb) expression of a successive interference cancellation (SIC) system for MRC and PDC schemes. The performance bounds were also derived and depicted for identically independent distributed variances at the receiving ends. It is found that the MRCSIC has higher performance for equal variances at the receiving antennas. On the other hand, the PDCSIC performs better when the variances are i.i.d. Keywords: CDMA, MIMO CDMA, diversity, impulsive noise, robust detection, VBLAST, SIC, channel estimation, time mismatch, multiuser detection.
Doctor of Philosophy in Electrical and Electronic Engineering. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Electrical and Electronic Engineering, 2012. Supervisor: Assoc. Prof. Dr. Aykut Hocanın.
Keywords: Electrical and Electronic Engineering; Wireless Communication Systems; Code Division Multiple Access (CDMA) - Multiple Input and Multiple Output (MIMO) CDMA - Diversity - Impulsive Noise; Robust Detection - Vertical - Bell Layered Space Time (VBLAST) - Successive Interference Cancellation (SIC); Channel Estimation - Time Mismatch - Multiuser Detection